Magnetothermoelastic vibrations on a viscoelastic microbeam subjected to a laser heat source - Abouelregal, A.E.; Zenkour, A.M. (Archives of Mechanics, 2021)
The linear theory of viscoelasticity remains an important field of research like most solids and polymer materials when exposed to a vicious dynamic loading effect. This article introduces a new model for describing the behavior of thermoviscoelastic microbeams considering the effects of temperature change and the longitudinal magnetic field. The governing equations in this model are derived based on the Euler–Bernoulli beam theory, Kelvin–Voigt model of viscosity, the generalized thermoelasticity, and the classical Maxwell equations. The two ends of the microbeam are clamped and subjected to the influence of a laser pulse with a temporal intensity profile. The analytical solutions to the physical fields are evaluated using the Laplace transform and its inversion transforms are performed numerically. The thermo-viscoelastic responses of the microbeam are calculated numerically and investigated graphically. The effect of different parameters such as viscosity, laser intensity, and the magnitude of the magnetic field are studied in detail.